2014
DOI: 10.1002/2013ja019410
|View full text |Cite
|
Sign up to set email alerts
|

Solar cycle dependence of nightside field‐aligned currents: Effects of dayside ionospheric conductivity on the solar wind‐magnetosphere‐ionosphere coupling

Abstract: In the present study we observationally address the role of ionospheric conductivity in the solar wind‐magnetosphere coupling in terms of global field‐aligned currents (FACs). Solar EUV irradiance changes during a solar cycle and so does its contribution to the ionospheric conductivity. We statistically examine how, under fixed external conditions, the intensities of the R1 and R2 currents and their demarcation latitude depend on solar activity (F10.7). An emphasis is placed on nightside FACs in the dark hemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Cliver et al, 2000, Svalgaard, 1977, which is often called the equinoctial effect. Merkin et al, 2003, Ohtani et al, 2014. This result may be interpreted in terms of the deformation of the dayside magnetosphere by the R1 current, which likely affects the efficiency of the SW-M-I coupling (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…Cliver et al, 2000, Svalgaard, 1977, which is often called the equinoctial effect. Merkin et al, 2003, Ohtani et al, 2014. This result may be interpreted in terms of the deformation of the dayside magnetosphere by the R1 current, which likely affects the efficiency of the SW-M-I coupling (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the region 2 (R2) FAC could possibly play a direct role in the formation of the midlatitude trough (Lyatsky and Mal'tsev 1981). Ohtani et al (2014) showed that R2 current is more intense in high solar activity. Therefore, the intensification of the R2 current in high solar activity can also lead to an increase of the trough depth.…”
Section: Resultsmentioning
confidence: 99%
“…Obvious candidates are ionospheric current and the M-I coupling system that are known to affect AL (Sato and Iijima 1979;Nagatsuma 2004;Ohtani et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between these two solar minima (1996 and 2009) is also seen in the global ionospheric density (Solomon et al 2013), which was simply explained by the difference in the solar EUV intensity between these two minima (see also Bergeot et al 2013). The relation between the solar EUV and the location of the current system is also examined by Ohtani et al (2014). Using satellite data to obtain the field-aligned current, they showed that the change in the location of the magnetosphere-ionosphere (M-I) current system depends on the F10.7 index and suggested that this could be the cause of the low Sun-Earth coupling during 2009.…”
Section: Introductionmentioning
confidence: 96%